Eficacia antiparasitaria de dos métodos de aplicación del látex de ojé, Ficus insipida sobre el ectoparásito Piscinoodinium pillulare presente en juveniles de Colossoma macropomum - Pereira Saavedra, Charles Davis (2022)
The objective of the present study was to evaluate the effect of the application mode of the Ficus insipida ojé latex for the control of the ectoparasite Piscinoodinium pillulare in Colossoma macropomum. Were sampled 600 juveniles of C. macropomum from an earthen pond of the NGO's Amazon Research Center Ornamental Fishes. Before evaluating the efficacy, the mean lethal concentration of F. insipida latex was determined at 96 hours of exposure (LC50-96h); being the fish subjected to doses of 0; 1; 5; 9; 13 and 17 mL/L, in a static system and the data were analyzed using the Probit regression. For efficacy, concentrations of 0, 1, 2, 3, 4 and 5 mL/L were evaluated in therapeutic baths of 10 minutes for 3 days and concentrations of 0, 1, 3 and 5 mL/L included in the food (administration orally) for 14 days. The LC50-96h for C. macropomum juveniles was 11.32 mL/L for F. insipida latex. In therapeutic baths, efficacy was registered from 10.71 to 71.68%, while the application in food registered efficacy from 4.93 to 6.66%. In conclusion, the F. insipida latex had an antiparasitic effect against the protozoan Piscinoodinium pillulare, with the application of 4 mL/L in prophylactic baths being the one with the highest efficacy.